2015
DOI: 10.1158/1541-7786.mcr-15-0068
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Dual Role of AMPK in Cancer: From Experimental to Human Studies

Abstract: The precise role of 5′AMP-activated kinase (AMPK) in cancer and its potential as a therapeutic target is controversial. While it is well established that activation of this energy sensor inhibits the main anabolic processes that sustain cancer cell proliferation and growth, AMPK activation can confer on cancer cells the plasticity to survive under metabolic stress such as hypoxia and glucose deprivation, which are commonly observed in fast growing tumors. Thus, AMPK is referred to as both a “conditional” tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
162
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 174 publications
(168 citation statements)
references
References 148 publications
4
162
0
Order By: Relevance
“…Additionally, inhibition of unchecked mTORC1 activity and de novo lipogenesis, results in applying metabolic tumor-suppressor role of the AMPK. It is of worth mentioning that both mTORC1 activity and de novo lipogenesis are required during G1-S and G2-M phases [3]. It is proved that there is an inverse relationship between de novo FA synthesis concomitant and phosphorylation of its major target ACC1, prior to cytokinesis initiation.…”
Section: Ampk As Tumor Suppressormentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, inhibition of unchecked mTORC1 activity and de novo lipogenesis, results in applying metabolic tumor-suppressor role of the AMPK. It is of worth mentioning that both mTORC1 activity and de novo lipogenesis are required during G1-S and G2-M phases [3]. It is proved that there is an inverse relationship between de novo FA synthesis concomitant and phosphorylation of its major target ACC1, prior to cytokinesis initiation.…”
Section: Ampk As Tumor Suppressormentioning
confidence: 99%
“…The mediation would take place under the close interaction between energy regulators and cancer pathogeneses. The presence of variety of subunits in AMPK implies the particularity of the tissues which can further contribute to growth of tumor cell and its independent reproduction [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the many connections between AMPK and cancer cell proliferation, mutations in the AMPK β1 subunit are not common in cancers (Forbes et al ., 2015) and recent studies have suggested that inhibition of AMPK may make cancer cells more sensitive to apoptosis (Jeon et al ., 2012; Shackelford et al ., 2013; Zadra et al ., 2015). Thus far, only one study has examined the effects of germline deletion of AMPK in a mouse model of tumorigenesis where the authors observed that deletion of the AMPK α1 isoform promoted B‐cell lymphoma when crossed to c‐Myc transgenic mice (Faubert et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%